On the Generalized Krätzel Transform and Its Extension to Bohemian Spaces - S. K. Q. Al-Omari; Adem Kılıçman (Abstract and Applied Analysis)
We investigate the Krätzel transform on certain class of generalized functions. We propose operations that lead to the construction of desired spaces of generalized functions. The Krätzel transform is extended and some of its properties are obtained.